Analyzing the Spatial Distribution of Urban Green Space and Identification of Its Potential Expansion Areas: A Case Study in Adama City, Ethiopia - Kefelegn, Wagamyelew (ASTU, 2023)
Today, some 55% of the world??s population 4.2 billion inhabitants live in cities. This trend is expected to continue. By 2050, with the urban population more than doubling its current size, nearly 7 of 10 people in the world were live in cities. Africa??s urban population increased more than sixteen-fold between 1950 and 2018, rising from 33 million to 548 million and is likely expected to nearly triple between 2018 and 2050. Ethiopia, has a very low level of urbanization 21.2% in 2019, is among the least urbanized but fast urbanizing countries in sub-Saharan Africa. Nowadays, land suitability analysis methods and geospatial technologies have been used to support urban green space planning in developed countries; however, its application and practices are limited in developing countries, like Ethiopia. Therefore these studies aimed at analyzing the spatial distribution of UGS in Adama City Ethiopia, and evaluate existing GS and then scientifically select potential expansion sites for its development. Based on the analysis the overall city per capita is about 5.15m2 with respect to the total population and total area in m2.Through object based image classification of planet image using the nearest neighboring algorithm, the LULC maps of the study area with the land use type of Bare Land, Built Up, Vegetation, Farm Land and Water Body was prepared. The suitability analysis was done by adopting GIS-based Multi-criteria analysis (MCA) using fuzzy analytical hierarchy process (FAHP) to selec
Keywords: Adama, UGS, FAHP, MCDM, OBIA, Spatial Distribution, potential site